Bupleurum chinense exerts a mild antipyretic effect on LPS-induced pyrexia rats involving inhibition of peripheral TNF-α production - Kang, Yuan; Gao, Yuan; Li, Ximeng; Guo, Xinwei; Liu, Zhuangzhuang; Li, Wenjing; Wei, Jianhe; Qi, Yun (Journal of ethnopharmacology, 2023)
Bupleuri Radix, the dried roots of Bupleurum chinense DC. (BC) or Bupleurum scorzonerifolium Willd., is one of the most frequently used traditional Chinese medicines. As the species in Xiao-Chai-Hu decoction, BC has been used as an antipyretic medicine with a long history. However, its antipyretic characteristics and underlying mechanism(s) remain unclear. To elucidate the antipyretic characteristics and mechanism(s) of BC used in its traditional way. The water extract of BC (BCE) was prepared according to the traditional decocting mode. Murine fever and endotoxemia models were induced by intravenous injection of lipopolysaccharide (LPS). In vitro complement activation assay and the levels of TNF-α, IL-6, IL-1β, and C5a were determined by ELISA. BCE exerted a confirmed but mild antipyretic effect on LPS-induced fever of rat. In vitro, it significantly lowered LPS-elevated TNF-α in the supernatant of rat complete blood cells and THP-1 cells, but failed to decrease IL-6 and IL-1β. In murine endotoxemia models, BCE markedly decreased serum TNF-α, but had no impact on IL-6 and IL-1β. BCE also restricted complement activation in vitro and in vivo. Nevertheless, the mixture of saikosaponin A and D could not suppress supernatant TNF-α of monocytes and serum TNF-α of endotoxemia mice. The present study dissects the peripheral mechanism for the antipyretic effect of BC used in the traditional way. Our findings indicate that BCE directly suppresses monocyte-produced TNF-α, thus decreasing circulating TNF-α, which may be responsible for its mild but confirmed antipyretic action. [Display omitted] •BCE exerts a confirmed but mild antipyretic effect on LPS-induced fever of rats.•BCE markedly decreases TNF-α, but not IL-6 and IL-1β, in vitro and in vivo.•BCE restricts complement activation in vitro and in vivo.•The mixture of saikosaponin A and D fails to suppress TNF-α in vitro and in vivo.